Fish Marketing Status with Formalin Treatment in Bangladesh - Shatabdi Goon; Munmun Bipasha; Md. Saiful Islam; Md. Bellal Hossain (International Journal of Public Health Science (IJPHS), 2014)
Fish possess an extremely strong cultural attachment considering irreplaceable animal food source in Bangladeshi diet beset with nutritional importance. It has been getting endangered by abominable practice of formalin in marketing leaded by some deceitful traders counting profit beyond ethical attainment and endangering public health. This paper outlines the formalin extremity with a several years practice in fish marketing involving almost 5% city markets with a petty heterogeneity comprising contrastive and potential strategy with formalin access. Regardless, this formalin corruption affiliated with deleterious health aggravations both for traders and consumers, comes out with impotency in workforce contravening economical influence on overall national prosperity.